Lingkungan Hidup Dan Pengelolaan Sumberdaya Alam Dalam Perspektif Islam - Malik, Abdul (Jurnal Lingkungan Almuslim, 2022)
This paper discusses the environment and natural resource management in an Islamic perspective from the author's perspective based on the limited amount of Islamic literature that the author knows. The discussion starts from defining the environment, analyzing human behavior towards the environment, human behavior and environmental destruction, human efforts in environmental conservation. It also discussed ethics and the environment, and finally religious views, especially Islam on the environment and natural resource management as well as environmental conservation orders, both recorded in the holy book as well as in history and hadith. Information was collected based on a literature review of research results and previous records as well as the results of observations of the environment itself.